UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS STRUKTURED DYADIC METHODS (SDM) - Tuah, Sahlan; Harahap, Andes Fuady Dharma; Ariaji, Rizky (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The problem in this study is the improvement of student biology learning outcomes which are one of the most important things in the learning process. The purpose of this study is to determine the improvement of learning outcomes of student activity biology and abilities through the application of learning models based on Structured Dyadic Methods (HR) on Waste and Recycling material in class X.IPA.1 SMA Negeri 1 Panyabungan Utara academic year 2017-2018. This type of research is classroom action research. Where the subject of the study was class X.IPA students of SMA Negeri 1 Panyabungan Utara consisting of 25 students. While data collection techniques and tools are tests and observations. The biology learning outcomes test of cycle I students was 76% and cycle II was 84.33%. Increased student activity levels in cycle I by 68.00% and in cycle II by 86.40% then increased teacher ability in managing learning cycle I by 75.00% and cycle II 91.00%.